Challenges of Implementing Strategic Management Accounting and Innovative Culture - Novie Susanti Suseno (UIN Sunan Gunung Djati, 2023)
Strategic management accounting (SMA) is important for every organization to achieve its strategic goals. This is because SMA can provide significant added value by providing the relevant information that modern organizations need to successfully achieve competitive advantage. The aim of this study is to investigate the application of SMA techniques in building a culture of innovation in creative industry companies in Garut district. This research contributes to knowledge that can provide an overview of the challenges in implementing strategic management accounting in adopting strategic management accounting innovations holistically. This research uses a qualitative approach. The informants in this research were 5 company managers and strategic management experts as sources person. The research results show that companies are faced with several challenges, such as managers being required to understand accounting and the ability of managers to make strategic decisions by paying attention to environmental changes that occur. The stages of SMA techniques to achieve a culture of innovation are by carrying out strategic benchmarking and performance benchmarking, competitive position monitoring, performance measurement system, competitor cost estimation and pricing strategy. By implementing SMA Techniques, this really helps the Company in improving its culture of innovation. By studying environmental changes, which are fully oriented towards meeting customer expectations, this has an impact on the team's work culture becoming more innovative.